The Influence of Online Shopping Experience, Consumer Reviews, and Social Factors on the Purchase Decisions of Psychology Students on Shopee - Julianus Barus; Kristi Endah Ndilosa Ginting; Mella Yunita (SEAN Institute, 2026)
This Shopee research included students from Prima Indonesia University's Faculty of Psychology. This study sets out to discover how psychological students use Shopee and what role social influences, online shopping experiences, and customer reviews play in their purchasing decisions. Quantitative methods were employed. One hundred and thirtyfive undergraduates from Prima Indonesia University's Faculty of Psychology made up the study population, with one hundred and ten serving as the sample. According to the study's findings, a partial t-test indicated that (1) online shopping experience (X1) did not significantly affect purchase decisions (Y). This is proven by the calculated t value of 1.915 <t table 2.035 and a significance value of 0.057> 0.05. (2) The t-test partially demonstrated that consumer reviews (X2) significantly influenced purchasing decisions (Y). A significant level of 0.008> 0.05 and a calculated t-value of 2.675>t-table 2.035 show this. (3) Social Factors (X3) were determined to have a substantial impact on Purchasing Decisions (Y) in a partial t-test. The t-value of 2.566, which is greater than the t-table value of 2.035, proves this. (4) The F-test showed that Y is affected by online buying experience (X1), customer reviews (X2), and social variables (X3) all at the same time. Reasons for this include a significance level of 0.009 > 0.05 and an F-value of 4.889 > F-table.